Flexible Protective Film: Ultrahard, Yet Flexible Hybrid Nanocomposite Reinforced by 3D Inorganic Nanoshell Structures. (25th February 2021) - Bae, Gwangmin; Choi, Gwang‐Mun; Ahn, Changui; Kim, Sang‐Min; Kim, Wonsik; Choi, Youngjun; Park, Dawon; Jang, Dongchan; Hong, Jung‐Wuk; Han, Seung Min; Bae, Byeong‐Soo; Jeon, Seokwoo
Abstract: Emerging flexible optoelectronics requires a new type of protective material that is not only hard but also flexible. Organic–inorganic (O–I) hybrid materials have been used as a flexible cover window to increase wear resistance and polymer‐like flexibility. However, the hardness of O–I hybrid materials is much lower than that of metals and ceramics due to the low intrinsic hardness of the organic matrix and limited volume fraction of inorganic reinforcement. Herein, a new type of hybrid nanocomposite combining an O–I hybrid material with continuous and ordered 3D inorganic nanoshell as an additional reinforcement is proposed. The 3D alumina nanoshell uniformly embedded in the epoxy‐siloxane molecular hybrid (ESMH) enables a rule of mixture without a loss in flexibility. Two types of reinforcements comprising siloxane molecules and 3D alumina shell ensure a metal‐like hardness (1.3 GPa), which is significantly higher than that of the typical polymers and polymer nanocomposites. The 3D hybrid nanocomposite films show superb impact resistance due to the 3D alumina nanoshell that effectively suppresses crack propagation. Inch‐scale 3D hybrid nanocomposite films also endure 20 000 bending cycles without failure and maintain high transparency (>82.0% at 550 nm) in the visible regions. Abstract : Hard yet flexible 3D hybrid nanocomposites are fabricated. The combination of organic–inorganic (O–I) hybrid material with 3D alumina nanoshell structures ensures significantly higher hardness and impact resistance. The inch‐scale 3D hybrid nanocomposite film also shows superb transparency and flexibility, suitable to flexible protective film.